CHEMICAL COMPONENTS OF MARINE AEROSOL OVER THE ANTARCTIC SEA - ニシカワ, マサタカ; ミゾグチ, ツグオ; カナモリ, サトル; カナモリ, ノブコ; アオキ, シュンジ; カワグチ, サダオ; NISHIKAWA, Masataka; MIZOGUCHI, Tsuguo; KANAMORI, Satoru; KANAMORI, Nobuko; AOKI, Shuhji; KAWAGUCHI, Sadao (1990)
P(論文) Fifty-eight samples were collected over the Antarctic Sea between December 3 and 31 in 1987. The sampling was carried out on board the research vessel "SHIRASE" by a medium volume sampler, which can be automatically operated every 12h at the sampling rate of 150l/min. The samples were analyzed for Na, Mg, Al, K, Ca, V, Mn, Fe, Ni, Cu, Zn, Sr, Mo, Ag, Cd, Ba and Pb for ICP-AES, and for NH_4^+, Cl^-, NO_3^- and SO_4^<2-> by ion chromatography. It is considered that aerosol derived from the crust has a concentration on the order of 10ng/m^3 over the Antarctic Sea. This estimated value is about 1/10 that over the East China Sea near Japan. The excess sulfate aerosol has a concentration on the order of 100ng/m^3 over that sea. Thus, the excess sulfate aerosol was defined as follows : (excess SO_4=SO_4-0.25×Na)_ Because of the mole ratio between excess SO_4^<2-> and Na, which was comparable to the amount of Cl loss on a mole basis, it must be present the combination as Na_2SO_4. It is considered that Cl loss is due to the reaction of sea salt aerosol with sulfate aerosol even over the Antarctic Sea. departmental bulletin paper